2006
DOI: 10.1021/ef060239m
|View full text |Cite
|
Sign up to set email alerts
|

Steam Gasification of Refuse-Derived Fuel (RDF):  Influence of Process Temperature on Yield and Product Composition

Abstract: The opportunity of using refuse-derived fuel (RDF) to produce fuel gas seems to be promising, and particular attention has been focused on alternative process technologies such as pyrolysis and gasification. Within this frame, present work relates to experimental tests and obtained results of a series of experimental surveys on RDF gasification with steam, performed by means of a bench-scale rotary kiln plant at different process temperatures, using thermogravimetry (TG) and infrared spectrometry (Fourier tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 20 publications
1
22
1
Order By: Relevance
“…The temperatures used for pyrolysis and gasifi cation were in the range 700°-1000°C at intervals of 50°C. The residence time of gases in the reactor was estimated to be from 8.8 to 11.6 s, according to the equation given by Galvagno et al 19 For each experimental run, the internal temperature of the reactor was kept at a constant elevated temperature. As shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The temperatures used for pyrolysis and gasifi cation were in the range 700°-1000°C at intervals of 50°C. The residence time of gases in the reactor was estimated to be from 8.8 to 11.6 s, according to the equation given by Galvagno et al 19 For each experimental run, the internal temperature of the reactor was kept at a constant elevated temperature. As shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…H 2 and CO contents increased sharply with the increase of the reactor temperature, while CO 2 , CH 4 , C 2 H 4 and C 2 H 6 contents exhibited the opposite tendencies, whereas syngas that has a H 2 / CO molar ratio in the range of 1-2 is highly desirable as feedstock for Fischer-Tropsch synthesis for the production of transportation fuels [30]. Furthermore, syngas reached highest level of 66.30 mol% at 900 8C.…”
Section: Influence Of Temperaturementioning
confidence: 97%
“…Further, the pyrolytic liquids were found to have relatively low calorific value, but contained 63% of the potential energy in the initial biomass feed and had a much greater density than the original biomass. The steam gasification of RDF was carried out by Galvagno et al (2006) in a series of trials, by varying the process temperature (850-1050°C), to investigate the effect of process temperature on the properties of the products formed and found that higher temperature resulted in higher conversion of the total organic content, which accounts for the greater syngas production. Further, at higher temperatures, the H 2 content in the product gas is always in excess due to the contribution from water.…”
Section: Introductionmentioning
confidence: 99%